Wideband trans-impedance amplifier with bandwidth tuning for near infra-red spectroscopy bio-medical applications - Balasubramanian, Muthukumaran; Balasubramanian, Ramachandran (International Journal of Electrical and Computer Engineering (IJECE), 2024)
A wide band trans-impedance amplifier (WBTIA) with tunable bandwidth for near infra-red spectroscopy (NIRS) bio-medical applications is presented in this research article. The first stage of the proposed WBTIA is implemented by a modified inverter-cascode (InvCas) trans-impedance amplifier (TIA) with series and shunt inductive peaking for the bandwidth extension and a common-source amplifier as a second stage for gain boosting. Bandwidth tuning is achieved by a novel tuning mechanism with a fixed capacitor and tunable metal–oxide–semiconductor (MOS) capacitor with a control voltage. The fixed capacitor provides a coarse-grain bandwidth tuning whereas the tunable MOS capacitors are used for fine-grain bandwidth tuning. The WBTIA is designed in 45 nm technology and it achieved a maximum trans-impedance gain (TIG) of 84.91 dBΩ and 354.81 MHz bandwidth. The proposed WBTIA consumes 41.24 µW power from 1 V supply voltage. The input referred current noise at 100 MHz is 169 fA/sqrt (Hz) and the output noise voltage is 69.8 pV/sqrt (Hz).